2019
DOI: 10.3390/ijerph16234797
|View full text |Cite
|
Sign up to set email alerts
|

Can Financial Support Reduce Suicide Mortality Rates?

Abstract: After the launch of governmental financial support for the development of a regional suicide prevention programme, ‘Emergency Fund to Enhance Community-Based Suicide Countermeasure’ in 2009, suicide mortality rates in Japan have decreased from 25.7 (in 2009) to 16.5 (in 2018) per 100,000 population. Therefore, to explore the effects of governmental financial support on suicide mortality rates in Japan, the present study determined the relationship between the trends of empirical Bayes standardised Mobile Ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(116 citation statements)
references
References 19 publications
0
116
0
Order By: Relevance
“…Therefore, to quantify the effects of the regional implementation amounts of 10 EFECBSC sub-divisions, unemployment rate and GDP per capita on regional EBSMR trends, adopted stepwise multiple regression analysis was used. 10 Stepwise multiple regression analysis with p values of 0.05 and 0.10 for respective entry and removal (SPSS for Windows, version 26, IBM, Armonk, NY, USA) was used to explore the effects of implementation amounts of 10 EFECBSC sub-divisions, regional trends of unemployment rate and GDP per capita on regional EBSMR trends of three groups: male, female and male plus female. The assumptions of multiple regression models were verified by normal P-P plot for standardised residual regression (SPSS for Windows, version 26).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, to quantify the effects of the regional implementation amounts of 10 EFECBSC sub-divisions, unemployment rate and GDP per capita on regional EBSMR trends, adopted stepwise multiple regression analysis was used. 10 Stepwise multiple regression analysis with p values of 0.05 and 0.10 for respective entry and removal (SPSS for Windows, version 26, IBM, Armonk, NY, USA) was used to explore the effects of implementation amounts of 10 EFECBSC sub-divisions, regional trends of unemployment rate and GDP per capita on regional EBSMR trends of three groups: male, female and male plus female. The assumptions of multiple regression models were verified by normal P-P plot for standardised residual regression (SPSS for Windows, version 26).…”
Section: Resultsmentioning
confidence: 99%
“…14 EFECBSC enhanced regional welfare and social safety nets, and improved regional social protection vulnerability. 10 Therefore, these data in Japan suggest the possibility that financial support, such as EFECBSC, plays an important role in the reduction of suicide mortality via enhancement of regional welfare/social safety nets and the social protection system. Until recently, numerous public health studies reported that suicide mortality rates were increased by recessions and increasing unemployment rates.…”
Section: Open Accessmentioning
confidence: 94%
See 3 more Smart Citations